If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (u + -8)(u + 3) = 0 Reorder the terms: (-8 + u)(u + 3) = 0 Reorder the terms: (-8 + u)(3 + u) = 0 Multiply (-8 + u) * (3 + u) (-8(3 + u) + u(3 + u)) = 0 ((3 * -8 + u * -8) + u(3 + u)) = 0 ((-24 + -8u) + u(3 + u)) = 0 (-24 + -8u + (3 * u + u * u)) = 0 (-24 + -8u + (3u + u2)) = 0 Combine like terms: -8u + 3u = -5u (-24 + -5u + u2) = 0 Solving -24 + -5u + u2 = 0 Solving for variable 'u'. Factor a trinomial. (-3 + -1u)(8 + -1u) = 0Subproblem 1
Set the factor '(-3 + -1u)' equal to zero and attempt to solve: Simplifying -3 + -1u = 0 Solving -3 + -1u = 0 Move all terms containing u to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -1u = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -1u = 0 + 3 -1u = 0 + 3 Combine like terms: 0 + 3 = 3 -1u = 3 Divide each side by '-1'. u = -3 Simplifying u = -3Subproblem 2
Set the factor '(8 + -1u)' equal to zero and attempt to solve: Simplifying 8 + -1u = 0 Solving 8 + -1u = 0 Move all terms containing u to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -1u = 0 + -8 Combine like terms: 8 + -8 = 0 0 + -1u = 0 + -8 -1u = 0 + -8 Combine like terms: 0 + -8 = -8 -1u = -8 Divide each side by '-1'. u = 8 Simplifying u = 8Solution
u = {-3, 8}
| 2(-1-9y)+4y=5 | | 18x^2-84x+98= | | 6(4x-7)=3(8x+8) | | 10n^2-4=506 | | 4+18r-2=9r+98-3r | | 159-4x=41x+14 | | 2x^3+5x^2-3x+5=0 | | 10-9x=23-16x | | x+(x-8)=60 | | 6y+4y=90 | | (8y-4y^2)+(3y-9y^2)= | | (0.5*x^2)-(1.5*x)=0.375 | | (0.5*x^2)-(1.5*x)-0.375=x | | q^2+2q=1 | | 2x^2-18x-8=0 | | 3x+30=10x-54 | | x^2-4.1x+2.2=0 | | (x^4)+(15x^2)-16=0 | | -7.5x=60.0 | | 3n-7=29 | | 0.7-10=0.5 | | 12t=-51 | | 9r=-36 | | x^2((x^2)+15)-16=0 | | -6(2b+3)+(13b-3)=0 | | 36c^2=4c | | 6x^2-16-20x=0 | | 36c^2=4v | | 2(3+6x)-4=50 | | 2.5q-1.2-2.1q=-0.6q-2.7 | | 6-3(3x-2)=-24 | | x+2=-35000 |